Survey of Undergraduate Students' Perceptions through the Online Learning - asti gumartifa; Indawan Syahri; Masagus Sulaiman (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine how students’ perception of online learning during the Pandemic of COVID-19. Quantitative descriptive analysis was used to analyze the data. The researchers used a Google Form questionnaire as the instrument to obtain the data. The researchers used a Likert scale to examine the questionnaire and analyze the results. To find out how students’ perception of online learning during the Pandemic of Covid -19, ten questions of questionnaires were evaluated. The result of study indicated various students’ perspective to the online learning implementation. The various perceptions came from different situation such as environment, family, finance, and others.The highest percentage of positive perceptions regarding to online learning was from the students at University of Tridinanti Palembang and continued from the students at University of Muhammadiyah Palembang, then the students at Collage of Agriculture and Science Palembang, and the last was from students of Islamic University of Raden Fatah Palembang. Furthermore, some students also showed low percentage of neutral and negative perception. Therefore, universities and lecturers must work together to minimize the negative sides of online learning, as well as optimize the advantages of the internet and technology.